Biochemical content and yield of some cultivars of green bean (Phaseolus vulgaris L.) under Moscow region conditions - A. A. Antoshkin; A. V. Molchanova; A. M. Smirnova (Овощи России, 2022)
Relevance. Increased demand in Russia for common bean (Phaseolus vulgaris L.) varieties of domestic breeding has stimulated the Federal Scientific Vegetable Center of breeding to intensify research on the creation of new asparagus bean varieties of vegetable direction.Materials and methods. Four vegetable bean varieties – Secunda, Lika, Ulyasha, Si Bemol of the laboratory of selection and seed production of vegetable Legume crops of the Federal Scientific Vegetable Center were used as the material for the study. The counts and observations were made according to the Methodology of the State Variety Trial of Agricultural Crops, 1975. The count of productivity was carried out in the technical stage of ripeness by replications. Harvesting was carried out when the biological stage of ripeness was reached. Biochemical studies of plants were carried out in the laboratoryanalytical department of the FSBSI FSVC. The biochemical composition of vegetable bean (green bean) varieties was studied according to the following indicators: determination of the total content of water-soluble antioxidants, ascorbic acid, dry matter, polyphenols, monosaccharides, total sugar content and starch.Results. Evaluation of samples by aggregate factors contributes to the selection of the most promising and high-quality varieties for their introduction into production. As a result of the research of vegetable bean on the main economically valuable features and biochemical composition for the period from 2018 to 2020, the varieties Lika and Ulyasha were selected. They were distinguished by high productivity of beans and seeds. Green bean variety Lika was noted for the highest total content of water-soluble antioxidants, ascorbic acid and the total of sugars content, the green bean variety "lobio" Ulyasha - high content of polyphenols and the total of antioxidants in the alcohol extract. Stable high yield, adaptive potential and high quality of beans, confirmed by the results of biochemical evaluation, allow us to recommend these varieties for consumption by the population as part of the diet and as an alternative to meat and dairy products.